3-methylhistidine and clinical outcomes in maintenance haemodialysis patients. Issue 10 (2nd March 2022) - Bres, Emilie; Pagan, Cécile; Bouchara, Anaïs; Pastural, Myriam; Granjon, Samuel; Laville, Maurice; Fouque, Denis; Soulage, Christophe O; Koppe, Laetitia
ABSTRACT: Background: Chronic kidney disease is an important contributor to morbidity and mortality. 3-methylhistidine (3-MH) is the by-product of actin and myosin degradation reflecting skeletal muscle turnover. Markedly elevated 3-MH levels have been documented in uraemic patients, but the interpretation of high 3-MH concentration in maintenance haemodialysis (MHD) patients remains unclear. Indeed, it is not known whether elevated serum 3-MH levels are a marker of excessive muscle catabolism or a better lean tissue mass. Here, we evaluated the association between serum 3-MH levels and clinical outcomes in these patients. Methods: Serum 3-MH concentration was measured by reverse-phase liquid chromatography/tandem mass spectrometry in a cohort of MHD patients. We analysed the relationships between various clinical/laboratory indices, lean tissue mass measured by bioimpedance spectroscopy, mortality and cardiovascular (CV) events. Results: Serum 3-MH concentration was positively correlated with serum albumin, normalized protein catabolic rate (nPCR), simplified creatinine index (SCI) and lean tissue mass. Of 291 MHD patients, during a mean follow-up of 847 days, 91 patients died and 101 patients experienced a CV event. Survival was significantly better in patients with high 3-MH concentrations ( P = .002). A higher level of 3-MH was also associated with a lower CV mortality and lower incidence of CV events ( P = .015 and P < .001, respectively). Low serum 3-MH levels remained significantly associated with CV events but not with mortality after adjustment for demographic, metabolic and CV risk factors. Conclusion: Elevated serum 3-MH concentration appears to be a marker of better lean tissue mass and nutritional status. Low serum 3-MH is a robust and independent predictor of CV events in the MHD population. Graphical Abstract: